Le peuplement paléolithique de Côte d'Or (Bourgogne, France) dans son contexte regional = The paleolithic settlement in Côte d'Or (Burgundy, France) in its regional context - Djindjian, François (Archaeopress Archaeology, 2023)
The Côte d'Or in Upper Burgundy is a zone of passage between basins more than an area of permanent settlement, except in the most temperate periods of early prehistory. The Boccard cave, which has the most complete stratigraphic sequence in the region, is here the subject of a previously unpublished detailed monograph.